Natural hydrogen seeps identified in the North Perth Basin, Western Australia. (3rd September 2021) - Frery, Emanuelle; Langhi, Laurent; Maison, Mederic; Moretti, Isabelle
Abstract: Natural hydrogen seeps called fairy circles have been identified in Mali, Brazil, Russia, and United-States. Natural hydrogen is produced from a field in Mali for 7 years. The natural hydrogen system is still poorly understood and needs to be studied in new geological contexts as to streamline hypotheses on the system dynamics and elements into concepts. In Australia, numerous circular surface features, commonly called salt lakes or swaps, are visible from the sky but no existing work shows nor quantifies any hydrogen content in those features. In this study, we reviewed the existing literature on fairy circles as to determine and directly test with soil-gas measurements if hydrogen surface-emitting features are present in Australia. We determined best candidates to test with a multi-disciplinary approach linking geology, multi-physical imaging, and seismic interpretation. Soil-gas measurements showed persistent hydrogen concentration localized in the external ring of circular depressions aligned along the Darling Fault, a major crustal boundary between the granitic, mafic and ultramafic rocks of the Yilgarn Craton from the sedimentary rocks of the Perth Basin. This work is the proof that fairy circles, in the meaning of H2 emitting structures, are present in Australia and opens the door to new prospectivity pathways by evaluating original hypotheses on natural hydrogen generation, migration pathways and entrapment. This geological setting promotes deep serpentinization of ultramafic rocks as well as oxidation of iron-rich Archean rocks and mafic dikes as potential hydrogen sources that are both of massive potential economic value. This hydrogen can circulate and be entrapped as aqueous hydrogen in low-salinity aquifers or migrate in gaseous phase in fault zones up to intermediate structural reservoir or to the surface. Highlights: First discovery and field measurement of natural hydrogen seeps in Australia. Original hypotheses on natural hydrogen generation, migration pathways and entrapment. Link of the hydrogen seeps with the structural geological system.